(3GdeSJWGY ef GdRGO dCabQ GdYHGO GHf GdYeGOs - (3GdYeGOj, YHO GdQMef Hf eMeO Hf eMeO, (B1051 (3g`s ((3eLOj GdYeGQI YfO bHQ GdeQMhe aGjb HGTGs)
(3ChdgG (B:s
(3HYO GdHSedI ; fMeOc jG ef jSQ GdMLGL hHYO ajbhd YHO GdQMef Hf eMeO Hf YeGO GdOjf GdMfaj hgPg ahGFO TQjaI SdcJ HgG eSdc GdefSc Ydi ePgH CHj MfjaI hSejJgG GdeSJWGY ef GdRGO dCabQ GdYHGO GHf GdYeGO s
(3BNQgG (B:s
(3GdaQV CaVd ef HQ GdhGdOjf haj GdfhGRd GdML QGcHG CaVd ef GdeTj dGfg GdeTQhY ef aYdg Ydjg GdUdGI hGdSdGe hdCf GdeTj jLgO GdEfSGf hjSjA Ndbg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 332s
(3eYLe GdeDdajf (B2 / 121s
(3cTa GdXfhf (B2 / 1892s
(3gOjI GdYGQajf (B1 / 549s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs